Diagnosis of Superficial Gastric Lesions Together with Six Gastric Lymphoma Cases via Probe-Based Confocal Laser Endomicroscopy: A Retrospective Observational Study - Qian Chen; Heng-Hui Cheng; Shuang Deng; Dong Kuang; Chang Shu; Li Cao; Guang-Quan Liao; Qiao-Zhen Guo; Qi Zhou (Gastroenterology Research and Practice)
Objective. To evaluate the performance of probe-based confocal laser endomicroscopy (pCLE) in diagnosis of gastric lesions. Methods. An outpatient department- (OPD-) based retrospective study was conducted for patients with suspected upper gastrointestinal (GI) tract lesions who underwent pCLE between 2014 and 2016 at a tertiary hospital in China. Final diagnosis was based on the histopathological reports. CLE reports were compared to histopathological reports to evaluate the diagnostic ability, including sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), and diagnostic accuracy. Results. 322 of 380 patients were diagnosed with gastric lesions via pCLE, including inflammation and benign ulcers (n=110), atrophy and intestinal metaplasia (n=152), intraepithelial neoplasia (n=27), adenocarcinoma (n=27), and lymphoma (n=6). In total, the diagnostic ability of CLE in evaluation of gastric lesions showed sensitivity 72.4% (95% confidence interval (CI): 67.1–77.2%); specificity 93.1% (95% CI: 5.6–8.4%); PPV 72.4% (95% CI: 67.1–77.2%); NPV 93.1% (95% CI: 5.6–8.4%); and accuracy 88.9% (95% CI: 87.3–90.4%), respectively. We further observed the capability of pCLE in diagnosing six gastric lymphoma showing those affected mucosa densely infiltrated with identical and round-shaped abnormal cells. Immunohistochemistry analysis confirmed one patient with diffuse large B-cell non-Hodgkin’s lymphoma (DLBCL) and five with mucosa-associated lymphoid tissue (MALT) lymphoma. Conclusion. pCLE is an accurate tool for the detection of gastric lesions and shows optimal values of sensitivity and negative predictivity. Moreover, combining pCLE with white light endoscopy (WLE) may be a promising adjunct to conventional biopsy sampling in evaluating GI tract with suspected lymphoma.